Feeding Performance in Preterm Infants and Full Term Infants at 40 Weeks Postmenstrual Age - Gupta, Gunjan; Vijay Kumar, Kaniyanoor Venkatesan; Anitha, R.; Ninan, Binu (Journal of Nepal Paediatric Society, 2016)
Introduction: Feeding problems are commonly reported among preterm infants. As premature infants are born before adequate maturation, inadequate feeding capabilities are common among preterm infants. Feeding is an innate behaviour in a new born. Swallowing is evident in a foetus by 16th week of gestation (Tuchman, 1994). By 40th week of gestation, neural processes are expected to mature completely. Feeding is an innate behaviour in a new born. Swallowing is evident in a foetus by 16th week of gestation. By 40th week of gestation, neural processes are expected to mature completely. Since the premature infants are born before adequate maturation of the systems, it is not unusual for them to have inadequate feeding capabilities. Material and Methods: This study aimed to compare feeding performance in preterm (between 30 and 34 weeks GA) and full term infants at 40 weeks Post menstrual age. Seventy infants and their mothers served as participants. A close ended questionnaire documented the oral reflexes, oro-motor skills, oro-sensory skills and feeding history in infants. Results: Results were tabulated under feeding history, (viz; history of use of nasogastric feeding, duration of feeding, episodes of coughing/ choking and vomiting, fussing during feeding, noisy breathing) and oral skills. Significant difference in feeding behaviour was observed between the term and preterm infants at 40 weeks post menstrual age. Conclusion: Hence the need for Speech Language Pathologist to evaluate feeding behaviour at 40 weeks post menstrual age becomes necessary.